2012
DOI: 10.1007/s10551-012-1343-1
|View full text |Cite
|
Sign up to set email alerts
|

Ethical Consumption and New Business Models in the Food Industry. Evidence from the Eataly Case

Abstract: Individual and collective ethical stances\ud regarding ethical consumption and related outcomes are\ud usually seen as both a form of concern about extant market\ud offerings and as opportunities to develop new offerings. In\ud this sense, demand and supply are traditionally portrayed as\ud interacting dialectically on the basis of extant business\ud models. In general, this perspective implicitly assumes the\ud juxtaposition of demand side ethical stances and supply\ud side corporate initiatives. The Eataly s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
67
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(71 citation statements)
references
References 84 publications
1
67
0
3
Order By: Relevance
“…For our purposes, the focus is on products that are related to the place of origin; this means, once again, products usually referred to as typical; however, here the words 'ethnic' and 'exotic' are also used in order to underline that these chains are not univocally related with one specific location and, specifically, with proximity; rather, they offer a full range of products coming from a variety of places, from nearby to far distant ones [52,53]. In these kinds of chains the focal company is a multi-located retailer that may be nationally or internationally based that sells via outlets and/or on the web.…”
Section: Supply Chains For Food Specialties: the Case Of Retailers Spmentioning
confidence: 99%
“…For our purposes, the focus is on products that are related to the place of origin; this means, once again, products usually referred to as typical; however, here the words 'ethnic' and 'exotic' are also used in order to underline that these chains are not univocally related with one specific location and, specifically, with proximity; rather, they offer a full range of products coming from a variety of places, from nearby to far distant ones [52,53]. In these kinds of chains the focal company is a multi-located retailer that may be nationally or internationally based that sells via outlets and/or on the web.…”
Section: Supply Chains For Food Specialties: the Case Of Retailers Spmentioning
confidence: 99%
“…In a 2006 speech, the European Commissioner for Agriculture, Marian Fischer Boel, suggested that ethical foods could play a significant role in re-orienting Europe's food system for the 21st century [7]. Consumers are more and more aware of their consumption choices and their impact, and this awareness is particularly seen in food consumption where ethical considerations apply to product, brand and channel choices [8] [9].…”
Section: Ethical Food: Supply and Consumptionmentioning
confidence: 99%
“…On the demand side, ethical stances are able to shift consumers away from specific market offerings and moderate behaviors to be more responsive to ethical requirements [8]. Ethical consumption does not have a shared definition.…”
Section: Ethical Food: Supply and Consumptionmentioning
confidence: 99%
“…Triguero et al (2013) examined the firms' innovation strategies of the Spanish agrifood industry. Sebastiani et al (2013) illustrated the impacts of the firms' attitudes toward consumers on the food industry and gave some suggestions to food firms. On the other hand, governmental regulation attracts more and more attention.…”
mentioning
confidence: 99%
“…Regarding the researching tool, there are mathematical model approaches including the game theory approaches as well as the dynamic model technology (Carriquiry and Babcock 2007;Wissmann et al 2012), the general equilibrium technologies (Lofgren and Elsaid 1999;Esmaeili et al 2013), the nature experiment (Kong 2012) and the empirical research (Sebastiani et al 2013;Scott 2013;Triguero et al 2013).…”
mentioning
confidence: 99%